Saint Thomas Aquinas’ Theology and His Commentary on the Book of Psalms - Casanova, Carlos Augusto (Biblica et Patristica Thoruniensia, 2021)
This is a brief commentary of the Spanish bilingual edition of Aquinas’ Commentary to the Book of Psalms, by Carlos Casanova and Enrique Alarcón, with the outstanding introductions to each of its four volumes. It deals with the relevance of Biblical studies for the understanding of Aquinas’ theological work, the hermeneutical tools used by Aquinas when commenting the Book of Psalms, the contemporary representatives of the school of Biblical Thomism and the main lessons a reader could draw from Aquinas’ reading of the Book of Psalms.